Augmentation prévue du budget UE pour le boe uf - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Le budget de l'UE pour 2004 a introduit une augmentation de 4% dans le...